ANALISIS PENGARUH PRICE, LOCATION, SERVICE DAN WORD OF MOUTH TERHADAP CUSTOMER SATISFACTION PADA HOTEL MERLIN DENGAN PURCHASE DECISION SEBAGAI VARIABEL INTERVENING - Lily Purwianti; Jacky; Louis Hernandez; Bendi Safero (Bajang Institute, 2023)
The research aims to analyze the effect of price, location, service quality, and electronic word of mouth (e-WOM) on customer satisfaction mediated by purchasing decisions. The sample criteria taken in this study were the people of Batam who frequently visited the Merlin Hotel and had the intention to recommend it to other consumers. In this study using a model with 22 questions, the number of respondents for this research sample was 150 respondents. The research findings show that there is a significant positive influence between the location, service, price and e-wom variables on the mediating variable of purchasing decisions. In addition, it was found that there was a significant positive influence between location, service, price and e-word variables on customer satisfaction mediated by purchasing decisions.